Individual and community level factors of safe child feces disposal among youngest children in East Africa: a multilevel modeling analysis using recent national demography and health survey data - Bewuketu Terefe; Nega Tezera Assimamaw; Bogale Chekole (BMC, 2024)
Abstract Background The Joint Monitoring Program (JMP) for water supply and sanitation developed by the WHO and UNICEF defines safe child feces disposal practices as either burial or defecation into a toilet. Children become exposed to fecal-oral illnesses when their stools are not disposed of appropriately, and this vulnerability persists until all children's stools are properly disposed of. Data on the elements influencing child feces disposal in East Africa is scarce. Hence, this study aimed to assess the prevalence and associated factors of safe child feces disposal in East Africa. Methods Data from the Demographic and Health Surveys, which were collected between 2015 and 2022 in 10 East African nations, were used in this analysis. For a weighted 44,821 children under the age of two, we examined additional features as well as how child feces were disposed of. Both bivariable and multivariable multilevel logistic regression were carried out to choose potential components and identify important explanatory variables connected to the outcome variable. With 95% confidence intervals, adjusted odd ratios (AORs) were used to present the results. P values of ≤ 0.2 and < 0.05 were used to investigate significant factors in the binary and multivariable multilevel logistic regression models respectively. Results Approximately 65.54% (95% CI: 65.10, 65.98) of children's waste was disposed of properly. Women age from 35 to 49 years (AOR = 1.12, 95% CI: 1.05-1.19) 15-24 years old, primary (AOR = 1.62, 95% CI, 1.53,1.72), and secondary/higher education (AOR = 1.22, 95% CI, 1.14,1.31), women from highly educated community (AOR = 1.33, 95% CI, 1.22,1.46), employed (AOR = 1.29, 95% CI, 1.24,1.35), poorer(AOR = 1.51,95% CI, 1.42,1.61), middle(AOR = 1.67, 95% CI, 1.56,1.78), richer(AOR = 1.96,95% CI, 1.82,2.11), and richest(AOR = 2.08, 95% CI, 1.91,2.27), mass media exposure (AOR = 1.37,95% CI,1.31,1.44), community level mass media exposure (AOR = 1.23, 95% CI, 1.34,1.34), had ANC visit(AOR = 1.71, 95% CI, 1.55,1.88), modern contraceptive(AOR = 1.17, 95% CI, 1.12,1.23), health institution delivery (AOR = 2.22, 95% CI, 2.09,2.34), had an improved toilet facility (AOR = 1.12, 95% CI, 1.07,1.17), children who's their age group from 6 to 11 months old, (AOR = 2.12, 95% CI, 2.01,2.25) and 12-23 months old (AOR = 3.10,95% CI, 2.94,3.27) were the factors associated with higher odds of safe child feces disposal as compared to less than six months old children respectively. Finally, women from high community poverty level (AOR = 0.87, 95% CI, 0.79,0.95), and rural women were the factors associated with lower odds of safe child feces disposal (AOR = 0.91, 95% CI 0.85-0.98) compared to their counterparts respectively. Conclusions East Africa has a Slightly lower proportion of properly disposing of child feces. There was a strong correlation between characteristics such as residence, mother's age, education level, work status, place of delivery, ANC visit, child's age, wealth index, media exposure, and poverty. Acting on these factors and strengthening and using links between mother and child health care is, thus, strongly advocated.